2019
DOI: 10.1111/dom.13661
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal glucagon acutely increases energy expenditure without inducing hyperglycaemia in overweight/obese adults

Abstract: Aim: To assess the acute effects of 0.7 mg intranasal glucagon (ING) vs intranasal placebo (INP) on food intake and resting energy expenditure (REE).Methods: A single-blind, crossover study was conducted in 19 overweight/obese adults (15 men, 4 women). REE was assessed by indirect calorimetry over 90 minutes, after which appetite was assessed using a visual analogue scale, and ad libitum caloric intake was assessed. Plasma samples were obtained at baseline and at 15-minute intervals post-treatment up to 90 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…glucagon has also been demonstrated by a 13% increase in EE via intranasal ingestion of 0.7 mg of glucagon for 90 minutes in individuals with overweight or obesity (11). In a 2017 study, we performed the longest IV glucagon infusion (13 hours at 6 ng/kg/min) in individuals with obesity.…”
Section: Study Importancementioning
confidence: 99%
“…glucagon has also been demonstrated by a 13% increase in EE via intranasal ingestion of 0.7 mg of glucagon for 90 minutes in individuals with overweight or obesity (11). In a 2017 study, we performed the longest IV glucagon infusion (13 hours at 6 ng/kg/min) in individuals with obesity.…”
Section: Study Importancementioning
confidence: 99%
“…Furthermore, glucagon-induction of energy expenditure is suppressed when glucagon is co-infused with high concentrations of insulin [27]. While glucagon effects on thermogenesis are markedly suppressed in the prandial state, intranasal administration of as little as 0.7 mg glucagon is sufficient to increase energy expenditure by 207 kcal/day in overnight fasted subjects, despite only a transient 2-fold increase in circulating glucagon [28]. In summary, a series of human studies confirmed the acute thermogenic effect of glucagon and glucagon stimulation of energy expenditure seemingly depends on the feeding status with diminished ability of glucagon to stimulate energy expenditure in the prandial state and elevation of energy expenditure by about 100–200 kcal when infused during the pre-prandial state.…”
Section: The Effect Size Of Glucagon-induced Energy Expenditure Inmentioning
confidence: 99%
“…In summary, a series of human studies confirmed the acute thermogenic effect of glucagon and glucagon stimulation of energy expenditure seemingly depends on the feeding status with diminished ability of glucagon to stimulate energy expenditure in the prandial state and elevation of energy expenditure by about 100–200 kcal when infused during the pre-prandial state. Glucagon-induced energy expenditure is preserved in human subjects with obesity [25,28]. The magnitude of glucagon’s thermogenic effect is similar to that of the ß3-adrenergic receptor agonist mirabegron, which primarily targets the brown adipose tissue (BAT) (+203 kcal/day) [29] and is similar to the acute energy expenditure increase induced by cold exposure (+193 kcal/day) [28].…”
Section: The Effect Size Of Glucagon-induced Energy Expenditure Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from effects on glucose metabolism, IN glucagon exerts other, as yet poorly investigated, actions. For example, IN glucagon induces gastric hypotonia [41] and (0.7 mg) acutely increases energy expenditure without inducing hyperglycemia in overweight/obese adults [42] with no effect on food intake and appetite.…”
Section: Biology Of Intranasal Glucagonmentioning
confidence: 99%